Controlling SEI Formation on SnSb‐Porous Carbon Nanofibers for Improved Na Ion Storage. (8th February 2014) - Ji, Liwen; Gu, Meng; Shao, Yuyan; Li, Xiaolin; Engelhard, Mark H.; Arey, Bruce W.; Wang, Wei; Nie, Zimin; Xiao, Jie; Wang, Chongmin; Zhang, Ji‐Guang; Liu, Jun
<x xml:space="preserve">Abstract</x> Porous carbon nanofiber (CNF)‐supported tin‐antimony (SnSb) alloys are synthesized and applied as a sodium‐ion battery anode. The chemistry and morphology of the solid electrolyte interphase (SEI) film and its correlation with the electrode performance are studied. The addition of fluoroethylene carbonate (FEC) in the electrolyte significantly reduces electrolyte decomposition and creates a very thin and uniform SEI layer on the cycled electrode surface, which an promote the kinetics of Na‐ion migration/transportation, leading to excellent electrochemical performance. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>